Simplifying procedure for prediction of resistance risk in CML patients - Test of sensitivity to TKI ex vivo - Žáčková, Markéta; Macháčková-Lopotová, Tereza; Ondráčková, Zuzana; Kuželová, Kateřina; Klamová, Hana; Moravcová, Jana (Blood cells, molecules & diseases, 2016)
Tyrosine kinase inhibitors (TKIs) targeting BCR-ABL have dramatically improved chronic myeloid leukemia therapy. While imatinib remains to be the first line therapy, about 30% of patients develop resistance or intolerance to this drug and are recommended to switch to other TKIs. Nilotinib and dasatinib are currently implemented into the first line therapy and other inhibitors have already entered the clinical practice. This opens further questions on how to select the best TKI for each patient not only during the therapy but also at diagnosis. The individualized therapy concept requires a reliable establishment of prognosis and prediction of response to the available TKIs. We tested the ex vivo sensitivity of patient primary leukocytes to imatinib, nilotinib and dasatinib - two concentrations of each inhibitor for 48h incubation - and we evaluated the usefulness of such tests for the clinical practice. Besides reflecting the actual sensitivity to the therapy, our optimized simple tests were able to predict the outcome in 90/87% of patients, for the next 12/24months, respectively. According to these results, the presented ex vivo testing could help clinicians to select the appropriate drug for each patient at diagnosis and also at any time of the therapy.
Keywords: výsledek terapie; imatinib mesylát; viabilita buněk; protinádorové látky; Cell Line, Tumor; chronická myeloidní leukemie; chemorezistence; Cell Death; Cell Survival; Pyrimidines; buněčná smrt; inhibitory proteinkinas; Early predictors; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Treatment Outcome; leukocyty; Dasatinib; lidé; Humans; pyrimidiny; Leukocytes; dasatinib; Chronic myeloid leukemia; Resistance; Protein Kinase Inhibitors; Drug Resistance, Neoplasm; nádorové buněčné linie; Antineoplastic Agents; Imatinib Mesylate